Improving the feasibility of deprescribing proton pump inhibitors: GPs’ insights on barriers, facilitators, and strategies - Japelj, Nuša; Knez, Lea; Petek, Davorina; Horvat, Nejc (Frontiers in Pharmacology, 2024)
Introduction The prevalent overprescribing of proton pump inhibitors (PPIs) poses health risks from prolonged use. GPs play a key role in initiating deprescribing PPIs, so understanding their decision-making factors and strategies to improve feasibility is crucial. This study aimed to investigate the perspectives of GPs on deprescribing PPIs with a focus on identifying facilitators, barriers, and strategies to enhance feasibility in clinical settings. Methods A qualitative study involving semi-structured interviews was conducted with nine GPs or trainees. The thematic analysis of the interviews was conducted using NVivo R1 (2020). Results Four main categories were identified: 1) Inappropriate prescribing of PPIs, 2) Facilitators for deprescribing PPIs, 3) Barriers to deprescribing PPIs, 4) Feasibility of deprescribing PPIs. GPs acknowledged excessive and often inappropriate PPI prescribing, with a lack of deprescribing efforts mainly due to time constraints. Other key barriers included patient reluctance, fear of symptom recurrence, and unawareness of long-term risks. Patient-initiated request is key facilitator for deprescribing PPIs. GPs emphasized the need for collaboration with healthcare professionals, clear guidelines, improved digital support, increased physician availability, and raising awareness among providers and patients to enhance deprescribing feasibility. Discussion GPs are calling for a multifaceted approach to improve the feasibility of deprescribing PPIs, involving patient-centered approaches, systemic optimizations, support from other healthcare professionals, and provider-centered strategies to emphasize the importance of deprescribing PPIs.